Microstructure and mechanical performance of alkali-activated tuff-based binders. (May 2023) - Yu, Zihao; Zhang, Tongwei; Deng, Yongfeng; Han, Yue; Zhang, Tongwen; Hou, Pulin; Zhang, Guoping
Abstract: The production of coarse-grained aggregates and sands from tuff, a naturally occurring rock composed of primarily fine volcanic detritus, usually generates 20 wt% powder as a solid waste. This paper presents the attempt to synthesize two high-performance, low carbon footprint, binders using fine tuff powder: a tuff-based binder (TBB) and a tuff and ground granulated blast-furnace slag (GGBS)-based binder (T-GGBS). The maximum compressive strength, flexural strength, Young's modulus, and density of the NaOH and Na-silicate activated TBB cured at 60 °C for 28 days are 71.3, 17.0, 2100 MPa, and 1892 kg/m 3 respectively, while those for the T-GGBS are 73.3, 15.8, and 1980 MPa, and 1880 kg/m 3 . To reveal the mechanisms for their high performance, an array of microstructure characterizations were performed on both the raw materials and final binders. For the TBB, the surfaces of irregular angular crystalline constituents in the tuff powder are partially dissolved and activated, while the undissolved part plays a key role as skeletons, as evidenced by the decrease of crystalline phases but increase in the N-A-S-H with increasing the NaOH concentration. For the T-GGBS, the amorphous GGBS constituents are fully dissolved and hence change the main product from the N-A-S-H gel to N/C-A-S-H cross-linked gel etc. However, overdosage of the GGBS consumes the majority of NaOH but leaves little to the reaction of tuff particles, most of which hence just act as inert fillers rather than reactants in the final binders. The effects of porosity on the mechanical performance are also discussed with reference to conventional geopolymers. Highlights: Two alkali-activated tuff-based binders were synthesized with low carbon footprint. Their optimum strengths without and with 20 wt% GGBS reach 71.3 and 73.3 MPa. The tuff-based binders consist of partially reacted crystalline constituents. The added GGBS consumes most NaOH and leaves the tuff particles as inert fillers. NASH and C/NASH are the main cementitious products in the binders.